Eating Disorders During the COVID-19 Pandemic - Sella Kintania Sari (Indonesian Journal of Global Health Research, 2020)
The COVID-19 pandemic is currently underway, so the policy of keeping a distance and staying at home must be implemented. Information about the pandemic is increasing every day, raising concerns that can affect mental health. Eating disorders as a mental disorder related to eating behaviors has also been affected by this pandemic. This article was written with the aim of knowing the impact of the COVID-19 pandemic on eating disorders condition. The method used is literature review using articles (available in NCBI and google scholar) and a book published by American Psychiatric Association in 2013. The keywords used in searching for articles are COVID-19, eating disorder, mental health, and pandemic so that 25 articles obtained and 21 articles (from 2018-2020) used in this literature review, and then an analysis is carried out using the systematic literature review method. Several studies have shown the negative impact of the COVID-19 pandemic on mental health. In research related to eating disorders, it was found that the COVID-19 pandemic can affect both individuals with eating disorders and the general population, and also affect the care for patients with eating disorders. The analysis of several articles shows that the COVID-19 pandemic can exacerbate the state of eating disorders and can increase the risk of developing eating disorders. The COVID-19 pandemic has also led to changes in care provided to patients with eating disorders where safety procedures must be implemented and telehealth becomes an alternative approach.